Breeding of Vicious Animals - Junaid Akbar; Sami ul Haq (Journal of Islamic and Religious Studies, 2020)
The vicious animals are an important component of the echo system of our universe. The balance of the universe is based on the fact that all the elements present in it should be kept within their different limits. This study discusses in detail about the permissibility of killing the animals, those are vicious and harmful to human beings by all means. Moreover, some traditions state the act of killing the vicious animals having virtues; so how would it create a misbalance in the ecosystem if they would become extinct. The study would also highlight on the legal position in Islamic Law about breeding and building farms (whether at the governmental level or individually) for saving these species. This study concludes that the killing of animals that have been declared mustaḥabb or permissible or obligatory will be killed only if they start hurting and harming humans and other essential resources. Moreover, the true meaning of the narrations in this regard is that vicious animals in the wild arena will not be traced to kill them if they are not a real threat to humans and other resources. Eradication of vicious animals is not a good idea because the complete extinction of any element of the universe may result in the misbalance of the ecosystem and may pose a real threat to the environment and severe global changes.